Nicomedes Santa Cruz: la formación de un intelectual público afroperuano - Aguirre, Carlos (2013)
This article reconstructs the trajectory of Nicomedes Santa Cruz, one of the foremost Afro-Peruvian intellectuals of all times, whose presence in the public scene transcended a purely artistic ambit and extended to the terrain of social and political criticism. Nicomedes Santa Cruz was a public intellectual whose multifaceted work addressed the most pressing themes of his time: he was a critic of racism, imperialism and social inequality; he supported the Cuban Revolution; he committed himself to the reforms of the Juan Velasco Alvarado regime; and he promoted international solidarity. Likewise, he tried to combine a commitment to socialism with a defense of Afro-Peruvian culture and rights.